2016
DOI: 10.1002/ejoc.201501283
|View full text |Cite
|
Sign up to set email alerts
|

N‐Rich Fused Heterocyclic Systems: Synthesis, Structure, Optical and Electrochemical Characterization

Abstract: A new class of N-rich fused heterocyclic compounds containing the triazolo-triazine moiety was synthesized and studied by cyclic voltammetry, UV/Vis spectroscopy, X-ray diffraction, and first principle computations. All the compounds show reversible or quasi-reversible reduction processes, with reduction potentials easily tunable within the class. LUMO ener-gies as low as –3.95 eV have been measured. The UV/Vis spectra show highly structured absorptions, indicative of rigid molecular skeletons. The solid-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Such low LUMO value augured a potential use of 28 as a n-type active molecules for organic transistors and organic photovoltaics (Table 1, entries 4-7). 6 With the aim to establish quantitative structure activity relationship (QSAR) for antifungal activities of [1,2,4]triazolo [3,4-b][1,3,4]thiadiazines 30-31, log P and polarizabilities were calculated (Table 1, entries 8-9). 7 <Table 1 near here> Time-dependent density functional theory (TD-DFT) has been used to examine the relationship between molecular structure and the one-and two photon absorption properties of conjugated energetic molecules 4-amino-3,7-dinitro- [1,2,4]triazolo [5,1-c] [1,2,4]triazine derivatives.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such low LUMO value augured a potential use of 28 as a n-type active molecules for organic transistors and organic photovoltaics (Table 1, entries 4-7). 6 With the aim to establish quantitative structure activity relationship (QSAR) for antifungal activities of [1,2,4]triazolo [3,4-b][1,3,4]thiadiazines 30-31, log P and polarizabilities were calculated (Table 1, entries 8-9). 7 <Table 1 near here> Time-dependent density functional theory (TD-DFT) has been used to examine the relationship between molecular structure and the one-and two photon absorption properties of conjugated energetic molecules 4-amino-3,7-dinitro- [1,2,4]triazolo [5,1-c] [1,2,4]triazine derivatives.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Fusco et al have reported the condensation of such diamines with various cyclic 1,2-aromatic diketones 385 to furnish the corresponding multicyclic ring systems 386 (entry 1). 6 The reaction was carried out in acetic acid under reflux overnight. Symmetric compound 388 has been obtained by using tetraketone 387 (entry 2).…”
Section: 652(ii) Closure Of the Six-membered Ringmentioning
confidence: 99%
“…Scheme 262 , Section 6.2.1 , for an acenaphthylene analogue). 342 LUMO energy levels were calculated to be −3.77 eV and −3.95 eV for 171.6 and 171.7 , respectively, indicating their potential utility as n-type semiconductors. Condensations with pure enantiomers of 2,2′-diamino-1,1′-binaphthalene 171.1 furnished the chiral systems 171.2 – 3 containing twisted 1,4-diazocine rings.…”
Section: Pyrenoidsmentioning
confidence: 99%
“…Fusco et al ( 2016 ) applied the condensation between α-diamines 254 and α-diketones 255a–e to obtain triazolo[4,3- b ][1,2,4]triazines 256 in 25–95% yield (the lowest yield for a system with two diketone moieties). An analogous result was obtained for 1,2,5-thiadiazole-3,4-diamine 257 (Planells et al, 2014 ; Figure 20 ).…”
Section: Main Partmentioning
confidence: 99%